Acute mountain sickness: Do different time courses point to different pathophysiologic mechanisms? - Berger, Marc Moritz; Sareban, Mahdi; Bärtsch, Peter (Journal of applied physiology, 2020)
Acute mountain sickness (AMS) is a syndrome of non-specific symptoms (i.e. headache, anorexia, nausea, vomiting, dizziness, and fatigue) that may develop in non-acclimatized individuals after rapid exposure to altitudes ≥2500 m. In field studies, mean AMS scores usually peak after the first night at a new altitude. Analyses of the individual time courses of AMS in 4 studies performed at 3450 m and 4559 m revealed that 3 different patterns are hidden in the above described overall picture. In 41% of those who developed AMS (i.e. AMS-C score >0.70) symptoms peaked on day 1, in 39% symptoms were most prominent on day 2, and in 20 % symptoms were most prominent on day 3. We suggest to name the different time courses of AMS type I, type II, and type III, respectively. Here we hypothesize that the variation of time courses of AMS are caused by different pathophysiologic mechanisms. This assumption could explain why no consistent correlations between an overall assessment of AMS and single pathophysiologic factors have been found in a large number of studies over the last 50 years. In this paper we will briefly review the fundamental mechanisms implicated in the pathophysiology of AMS and discuss how they might contribute to the three different AMS time courses.